Competitive modelling in speed climbing - Shunko, A.; Kravchuk, T. (BIO Web of Conferences, 2020)
The article analyzes the available scientific and methodological literature about training in the discipline of speed climbing. The speed climbing wall is described. It is divided into three parts with different characteristics, to clarify the specifics of the competitive distance. The physiological characteristics of competitive activity in speed climbing were studied.